Pelatihan Batik Ecoprint Daun Jati untuk Meningkatkan Kreativitas dan Peluang Usaha Kader PKK Tanjung Morawa - Elfi Husnita Hasibuan; Retno Desti Dwi Meilasari; Annisa Riski Rambe; Gustina Zahra Harahap (Universitas Negeri Gorontalo, 2026)
The creative economy has become one of the strategic sectors in improving community welfare through innovation and environmentally friendly products. One of the potential creative industries is textile crafts developed using eco-fashion principles, namely ecoprint. This community service program aimed to improve the knowledge and practical skills of PKK members in Tanjung Morawa Village, Deli Serdang Regency, through teak leaf ecoprint training. The implementation method consisted of lectures, demonstrations, hands-on practice, and participatory evaluation. Twenty PKK members participated in the training under the guidance of three instructors. The results showed increased participant understanding and skills in producing ecoprint fabrics using natural dyes from teak leaves. Participants also demonstrated high enthusiasm in developing ecoprint products into fashion and household crafts with economic value. This activity contributed to strengthening community capacity in developing environmentally friendly creative businesses based on local resources. The training is expected to become a sustainable community empowerment program that supports the development of the local creative economy.